PATIENT'S SATISFACTION COME FOR EXAMINATION AND REATMENT AT MEDICAL FACILITIES IN VIETNAM. SYSTEM OVERVIEW STUDY, PERIOD 2010-2020 (Vietnam Journal of Community Medicine, 2021)
Background: Patient’s satisfaction is a measure of the health facilities’ reputation and quality of health services. Therefore, determining the satisfaction of the patients in the current context is extremely necessary and meaningful. It provides the evidence for quality improvement of health services.Objective: A systematic review to review research findings on the the satisfaction level and relevant factors, analysis of strengths, weaknesses and deficiencies that need to be supplemented by further studies.Methods: Systematic review.Results: Searched and analyzed 32 national studies related to patient satisfaction. The results show that studies were carried out on many different subjects and locations with different levels of satisfactionConclusion: The satisfaction level of patients is quite high (satisfaction rate is over 70%, average score is over 3.5). Factors with high satisfaction rates include: Information transparency; Behavioralattitude and professional capacity of medical staff. Factors with not high satisfaction rates include: Infrastructure; Accessibility; Service results. Relevant factors: Patient’s satisfaction is not / verylittle related to demographic factors such as: Age, occupation, education level, medical examination target (with health insurance / no health insurance). Factors related to the patient’s satisfaction levelinclude: waiting
Keywords: Patients satisfaction, related factors; Systematic review, health facilities